Prognostic significance of combined score of fibrinogen and neutrophil-lymphocyte ratio for functional outcome in patients with aneurysmal subarachnoid hemorrhage - Hou, Yuyang; Li, Hua; Yang, Hongkuan; Chen, Rudong; Yu, Jiasheng (Frontiers in Neurology, 2022)
Objective To explore the relationship between fibrinogen and neutrophil to lymphocyte ratio (F-NLR) score and functional outcomes after aneurysmal subarachnoid hemorrhage (aSAH). Method A retrospective study was conducted that involved all consecutive patients with aSAH admitted to our institution from March 2018 to October 2021. Factors, such as demographics, comorbidities, clinical characteristics, neuroradiological data, and laboratory parameters, were collected from institutional databases. All patients achieved neurological assessment using the modified Rankin Scale (mRS) score 3 months after discharge to clarify the functional outcomes. The results were classified as favorable (mRS score 0–2) and unfavorable (mRS score 3–6). Univariate and multivariable analyses were performed to identify the relevant factors between inflammatory markers and functional outcomes after aSAH. Subsequently, a receiver operating characteristic (ROC) curve analysis was conducted to evaluate the predicting performance of variables. A propensity score match (PSM) was performed to correct imbalances in patients' baseline characteristics. Results Finally, 256 patients with aSAH were included in the study cohort. A total of 94 (36.7%) patients had an unfavorable outcome. F-NLR scores were 0 [interquartile range (IQR) 0–1] and 1 (IQR 1–2) in patients with favorable and unfavorable outcomes, respectively (p < 0.001). After adjustment, the F-NLR score on admission remained significantly associated with unfavorable outcomes in patients with aSAH. In the multivariable analysis, the F-NLR score was regarded as an independent risk factor of unfavorable outcomes [odds ratio (OR) 3.113, 95% CI 1.755–5.523, p < 0.001]. In ROC analysis, the optimal cutoff value of the F-NLR score was 0.5 points. Two cohorts (n = 86 in each group) obtained from PSM with low F-NLR scores (0 points) and high F-NLR scores (1–2 points) were used for analysis. A significantly higher unfavorable functional outcome rate was observed in patients with high F-NLR scores (33.7 vs. 9.3%, p < 0.001). The area under the curve (AUC) values of F-NLR scores before and after PSM were 0.767 and 0.712, respectively. Conclusion Fibrinogen and neutrophil to lymphocyte ratio score was an independent risk parameter associated with unfavorable functional outcomes at 3 months after aSAH. A higher F-NLR score predicts the occurrence of poor functional outcomes.